Blockade of MMP14 Activity in Murine Breast Carcinomas: Implications for Macrophages, Vessels, and Radiotherapy - Ager, Eleanor I.; Kozin, Sergey V.; Kirkpatrick, Nathaniel D.; Seano, Giorgio; Kodack, David P.; Askoxylakis, Vasileios; Huang, Yuhui; Goel, Shom; Snuderl, Matija; Muzikansky, Alona; Finkelstein, Dianne M.; Dransfield, Daniel T.; et al. (JNCI : Journal of the National Cancer Institute, 2015)
Matrix metalloproteinase (MMP) 14 may mediate tumor progression through vascular and immune-modulatory effects. Orthotopic murine breast tumors (4T1 and E0771 with high and low MMP14 expression, respectively; n = 5-10 per group) were treated with an anti-MMP14 inhibitory antibody (DX-2400), IgG control, fractionated radiation therapy, or their combination. We assessed primary tumor growth, transforming growth factor β (TGFβ) and inducible nitric oxide synthase (iNOS) expression, macrophage phenotype, and vascular parameters. A linear mixed model with repeated observations, with Mann-Whitney or analysis of variance with Bonferroni post hoc adjustment, was used to determine statistical significance. All statistical tests were two-sided. DX-2400 inhibited tumor growth compared with IgG control treatment, increased macrophage numbers, and shifted the macrophage phenotype towards antitumor M1-like. These effects were associated with a reduction in active TGFβ and SMAD2/3 signaling. DX-2400 also transiently increased iNOS expression and tumor perfusion, reduced tissue hypoxia (median % area: control, 20.2%, interquartile range (IQR) = 6.4%-38.9%; DX-2400: 1.2%, IQR = 0.2%-3.2%, P = .044), and synergistically enhanced radiation therapy (days to grow to 800mm(3): control, 12 days, IQR = 9-13 days; DX-2400 plus radiation, 29 days, IQR = 26-30 days, P < .001) in the 4T1 model. The selective iNOS inhibitor, 1400W, abolished the effects of DX-2400 on vessel perfusion and radiotherapy. On the other hand, DX-2400 was not capable of inducing iNOS expression or synergizing with radiation in E0771 tumors. MMP14 blockade decreased immunosuppressive TGFβ, polarized macrophages to an antitumor phenotype, increased iNOS, and improved tumor perfusion, resulting in reduced primary tumor growth and enhanced response to radiation therapy, especially in high MMP14-expressing tumors.